Surgical and Clinical Outcome of Bipolar Hemiarthroplasty Over Unipolar Hemiarthroplasty in Case of Fracture Neck of Femur in Elderly- Done in CBMCH,B and Private Clinics (Community Based Medical Journal, 2016)
Back ground: Whether bipolar hemiarthroplasty[BH] for displaced femoral neck fractures has benefit over unipolar hemiarthroplasty[UH] remains controversial. Intracapsular fracture neck femur mainly occur in elderly person. The prime goal of treatment is to return the patient to their pre-fracture functional status. The surgical treatment is the treatment of choice, hip replacement arthroplasty (hemi or total) is a viable choice in treatment option. In this clinical study 96 elderly patients (age 55-78 years) with a displaced intracapsular femoral neck fracture were treatment over a six year period (December 2009 to December 2015). All of them underwent hemiarthroplasty either bipolar or unipolar, after appropriate medical and anesthetic fitness. The patients were reevaluated at two weeks, six weeks, at six months postoperative and assessed using mainly Harris hip score (HHS) and visual analogue scale (vas) for evaluation of clinical and surgical outcome Also x-ray done to seen erosion of acetabulam. The mean age of patients was 64.5 years and male female ratio 45.83% -54.17%. The mean HHS score was 83.5 for BH and 82.5 for UH at the end of the 6 months. The mean score on VAS scale was 4mm (mu) at 6 months for both BH and UH follow up visit. At the one year 03 cases of unipolar complications mild hip pain. No patients need revision surgery. Bipolar and unipolar hemiarthroplasty is the treatment of choice in elderly patient with displaced femoral neck fracture provides early ambulation, good functional outcome, pain free joint with minimal complications without the need for revision surgery. There is no significant differences between Bipolar and Unipolar arthroplasty surgically and clinically.CBMJ 2016 January: Vol. 05 No. 01 P: 27-32